2013
DOI: 10.1080/13691058.2013.845692
|View full text |Cite
|
Sign up to set email alerts
|

Circumstances, experiences and processes surrounding women's entry into sex work in India

Abstract: Evidence suggests that in India, the early stages of a woman's career as a sex worker may be an important period to target for HIV and sexually transmitted infection prevention. Before such an intervention is designed and implemented, it is necessary to first understand the life circumstances of women at the start of their sex work careers. We performed a review to bring together available literature pertaining to entry into sex work in India and to highlight knowledge gaps. We found that historical traditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…The study also found that improved financial security is a key driver in increasing consistent condom use. This is in line with previous studies which demonstrate that FSWs under poor financial conditions are more likely to engage in risky sexual practices [34][35][36]. Poor financial conditions have an inverse relationship with FSWs' ability to negotiate for condom use with their clients [37].…”
Section: Plos Onesupporting
confidence: 91%
“…The study also found that improved financial security is a key driver in increasing consistent condom use. This is in line with previous studies which demonstrate that FSWs under poor financial conditions are more likely to engage in risky sexual practices [34][35][36]. Poor financial conditions have an inverse relationship with FSWs' ability to negotiate for condom use with their clients [37].…”
Section: Plos Onesupporting
confidence: 91%
“…FSW face a unique set of occupational exposures that often place them at risk for mental health disorders. Many women enter sex work due to poverty (McClarty et al, 2014; Saggurti, Sabarwal, Verma, Halli, & Jain, 2011), which contributes to depression including factors such as hopelessness and insecurity (V. Patel & Kleinman, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6 illustrates that clients were the most common perpetrators of this violence, but members of the militsiya were also implicated. [23][24][25][26], and are less likely to access to HIV prevention services, when compared to older CSW [11; 12]. Indeed, national HIV reports indicate that young CSW (<25 years) in Zaporizhzhya, when compared to older CSW (≥25 years), are disproportionately burdened by HIV infection [27], and are less likely to have been tested for HIV in the past twelve months or reached by existing programmes offering HIV prevention services [28].…”
Section: Hiv Vulnerabilities and Overlapping Risk Behaviours Among Fementioning
confidence: 99%